ANALISIS KEMAMPUAN LITERASI SAINS MAHASISWA PENDIDIKAN BIOLOGI SEMESTER 2 PRODI PENDIDIKAN BIOLOGI - Ninda Nur Mahdiyyah, Ninda; Wijayanti, Erna (JPB - Jurnal Pendidikan Biologi, 2023)
Scientific literacy is the ability to use scientific information, recognize problems, and draw conclusions based on data to understand and make choices about the natural world and changes caused by human activities. Science literacy is essential to address a wide range of ethical, moral, and global challenges. This study aims to measure the science literacy ability of Biology Education students in semester 2 of the Biology Education Study Program. The study sample amounted to 22 people from a population of 129 people consisting of 4 classes. The data collection technique uses biological science literacy tests in the form of multiple choice. Data analysis techniques use descriptive analysis. Based on the results of data analysis, it was found that the science literacy ability of Biology Education students in Semester 2 in the medium category was 15%, and the low category was 7%. In the results of the value of science literacy ability on the indicator explaining phenomena scientifically, it can be seen that the average score obtained by all students is 14.25 which is included in the low category. The results of the value of biological science literacy ability on the indicator of evaluating and designing scientific investigations can be seen that the average score obtained by all students is 9.75 which is included in the low category. The results of the value of biological science literacy skills on data interpretation indicators and proving scientific data can be seen that the average score obtained by all students is 26.6 which is included in the low category. Based on the results of the data obtained, it can be concluded that the science literacy ability of biology students in semester 2 as a whole is in the low category.